If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 8 = 2y + 8 Reorder the terms: 8 + -4y = 2y + 8 Reorder the terms: 8 + -4y = 8 + 2y Add '-8' to each side of the equation. 8 + -8 + -4y = 8 + -8 + 2y Combine like terms: 8 + -8 = 0 0 + -4y = 8 + -8 + 2y -4y = 8 + -8 + 2y Combine like terms: 8 + -8 = 0 -4y = 0 + 2y -4y = 2y Solving -4y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -4y + -2y = 2y + -2y Combine like terms: -4y + -2y = -6y -6y = 2y + -2y Combine like terms: 2y + -2y = 0 -6y = 0 Divide each side by '-6'. y = 0 Simplifying y = 0
| 2(x+2)=6(x-3)-6 | | 7xy=329 | | x^3y=-2 | | -14=-2+n | | -23=-7x+54 | | -(r+2)=2(3r-3) | | -x-3=-2x+5 | | 3a-10=4a-8 | | 2-3n=32 | | a/2=a/30-2/30 | | 3(-2v+19)=1-20v | | 3x=11+7 | | 6(9-7)-3(4-q)=0 | | -60=-20+4x | | 4(x+3)=7-4(2x+5) | | -2(k+4)=6(6-4k) | | -15=m(4)+5 | | -22+x=84 | | 18(6x-6)-24x-26=-20 | | a/2=a-2/30 | | 3x-14=-4+8x | | 7x-1=5x-1 | | 2x-5-r=13+2r | | 3x-6=2(4x-18) | | 6(x+4)-7x=4(3x+1)-9x | | 15+k=3(14-2) | | R=5x+22 | | x+.08x=50 | | 3x-3-x-3= | | 7(3x-1)-(x+5)=.52 | | 3k+2(10+8k)= | | 5-1x=x+1 |